The Role of Influencer-Generated Contents to the Cognition and Emotional Attachment Among Generation Z Consumers in Manila, Philippines - Angeles, Rhea Jane G.; Clemente, Carmhiella A.; Malimban, Renoa Lorraine O.; Santos, Jean Erika G.; Tan, Jian Carlo D. (Future Science / FSH-PH Publications, 2024)
Along with the rising digitalization of businesses, social media influencers (SMI) have been essential in redefining how the online promotional system operates. In the Philippines alone, social media influencers are central to all online discussions. The country is known as the